213k views
5 votes
S varies inversely as G. If S is 5 when G is 2.4, find S when G is 6.

User Zans
by
6.7k points

1 Answer

2 votes

We have that s varies inversely as G.

Then, we have the next equation:


S=(k)/(G)

If S= 5 when G=2.4

Then:


\begin{gathered} 5=(k)/(2.4) \\ Solve\text{ for k} \\ k=12 \end{gathered}

Where k represents the constant.

If G=6, we need to find S using k = 12.

Therefore:


\begin{gathered} S=(12)/(6) \\ S=2 \end{gathered}

Hence, If G=6, then S=2.

User Navdroid
by
5.7k points